Tingkat Kemampuan Melempar Bola Pada Permainan Bocce Anak Tuna Grahita Ringan Peserta Didik Putri (SDLB) Negeri Wiradesa Kabupaten Pekalongan - Kresnapati, Pandu; Fatkhu Royana, Ibnu; Aji Setyawan, Danang (YLPK Mahardhika, 2024)
Special Education is intended for students who experience difficulties in the learning process due to physical, emotional, mental, intellectual, or social disorders, or have extraordinary intelligence and talent potential (National Education System Law of 2003). Children with physical, cognitive, and behavioural disorders generally receive educational services at Special Schools (SLB), which are special schools for children with special needs. This study used a